Pre-symptomatic prediction of morbitidies in preterm infants with patent ductus arteriosus by targeted neonatal echocardiography and brain-type natriuretic peptide - Yasser Elsayed; Mary Seshia; Reeni Soni; Ilan Buffo; Ronald J. Baier; Patrick J. McNamara; Shyamala Dakshinamurti (Hygeia Press di Corridori Marinella, 2016)
Objectives: Our objective was to compare patent ductus arteriosus (PDA) diameter, PDA score and brain-type natriuretic peptide (BNP) measurements at 48-72 hours of life, for prediction of neonatal morbidities. We hypothesized that use of a PDA score with BNP, may improve pre-symptomatic prediction of PDAs associated with adverse outcomes. Method: Infants < 31 weeks GA were prospectively studied by targeted neonatal echocardiogram (TNE) at 48-72 hours age, composite PDA score and serum BNP assay; the clinical team remained blinded. PDA was independently diagnosed by echocardiography at time of clinical suspicion (6 ± 2 days), and treated at discretion of the clinical team. Primary outcome was survival with one or more of adverse outcomes (intraventricular hemorrhage [IVH], bronchopulmonary dysplasia [BPD], retinopathy of prematurity [ROP], necrotizing enterocolitis [NEC]). Results: A PDA was present in 56 of 70 infants studied at 48-72 hours; 30 were eventually diagnosed with PDA but never required treatment, 19 required medical treatment, 7 surgical ligation. After adjustment for gestation, PDA diameter did not predict any adverse outcome, PDA score was associated with increased risk of any adverse outcome and high BNP was associated with IVH, BPD, or survival with any adverse outcome. Conclusions: Comprehensive PDA evaluation at 48-72 hours of age may predict the subsequent occurrence of adverse outcomes and may be useful to define the PDA treatment threshold.